A Diversification of Honey and Banana Extract in Vegetable Smoothies : Diversification of Honey and Banana Extract in Vegetable Smoothies to Improve the Health of Students at SMP Negeri 6 Kota Bima - Husnul Khatimah, Nur; Zuraini, Irma; Hamiah, Nurul; Alkhair; Sutriawan (Journal of Excellence Humanities and Religiosity, 2025)
Healthy food and beverage consumption patterns in adolescents play a crucial role in growth, development, and academic performance. Diversifying school menus through the introduction of vegetable smoothies has the potential to improve nutritional intake, holistic health, and student concentration. Objective: To introduce healthy beverage diversification based on vegetable smoothies and educate students of SMPN 06 Kota Bima about the importance of a balanced diet and the negative impact of consuming high-sweetened beverages. Methods: Community service was carried out through location surveys, administrative arrangements, material preparation, and program implementation. Methods included counseling with interactive lectures, questions and answers, and distribution of vegetable smoothies samples. The activity was held on May 07, 2024 at SMPN 06 Bima City, with the participation of 40 respondents. Results: The education program showed a significant increase in students' knowledge about healthy beverage diversification, especially vegetable smoothies enriched with honey and banana fruit extract. Post-intervention observations indicated an increase in students' interest and preference for healthy beverage consumption, indicating positive potential in changing consumption patterns and increasing adolescent nutrition awareness.